1997
DOI: 10.2105/ajph.87.2.221
|View full text |Cite
|
Sign up to set email alerts
|

Drug use disorders and treatment contact among homeless adults in Alameda County, California.

Abstract: OBJECTIVES: This study estimates the extent and distribution of specific drug problems among homeless adults. METHODS: A countywide probability sample of 564 homeless adults received structured interviews that included a standardized assessment of substance use disorders. RESULTS: Two thirds of the sample (69.1%) had a lifetime history of a substance use disorder (including abuse of or dependence on alcohol [52.6%] or drugs [52.2%]); half had a current (52.4%) substance use disorder (including alcohol [38.8%] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
68
1
4

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(83 citation statements)
references
References 21 publications
10
68
1
4
Order By: Relevance
“…Much like results in this study, those findings relate to difficulty exiting homelessness and to prolonged episodes of homelessness (Gregoire 1996;Zlotnick, Tam, and Robertson 2003). One reason for the association between substance abuse and prolonged housing instability may be that homeless women's substance use often goes untreated (Zima et al 1996;Robertson, Zlotnick, and Westerfelt 1997;Zerger 2002). Among homeless women with a substance use disorder, only onethird report contact with any treatment services during the prior year (Zlotnick et al 2003).…”
Section: Discussionsupporting
confidence: 64%
“…Much like results in this study, those findings relate to difficulty exiting homelessness and to prolonged episodes of homelessness (Gregoire 1996;Zlotnick, Tam, and Robertson 2003). One reason for the association between substance abuse and prolonged housing instability may be that homeless women's substance use often goes untreated (Zima et al 1996;Robertson, Zlotnick, and Westerfelt 1997;Zerger 2002). Among homeless women with a substance use disorder, only onethird report contact with any treatment services during the prior year (Zlotnick et al 2003).…”
Section: Discussionsupporting
confidence: 64%
“…5,6 Mental disorders are prevalent among homeless people, [7][8][9] with substance dependence the most common diagnosis among homeless populations across the Western world, occurring at rates far exceeding those among the general population. [10][11][12][13][14] A recent meta-analysis indicated that up to 59 % of homeless people are alcohol dependent, and 54 % are dependent on at least one illicit drug. 7 Other evidence suggests that more than half of homeless people with a substance use disorder suffer at least one comorbid psychiatric disorder.…”
Section: Introductionmentioning
confidence: 99%
“…58 Despite the scale of the issue and the targets set, many gaps remain in our knowledge of homelessness in Australia. Notably in this context, information on the prevalence of drug use among homeless people is substantial and clearly demonstrates a strong relationship, 10,12,14,15,17,59 yet data on homelessness among problem drug users are less readily available, having been collected only among restricted samples of drug users, such as those seeking treatment, 20 or participants of studies of HIV prevalence, incidence, and risk behaviors and risk reduction interventions. 34,48,[51][52][53] Since 1995, the Australian NSP Survey (ANSPS) has provided annual point prevalence estimates to monitor patterns of BBV infection and risk behaviors among needle and syringe program (NSP) clients.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] In a recent study, Howard et al 8 reported independent associations for tuberculin positivity and crack cocaine use, as well as alcoholism, among participants seronegative for human immunodeficiency virus (HIV). Given the connection between substance abuse and TB, along with high rates of reported drug use and abuse, [9][10][11][12] and of alcohol use and abuse among homeless persons, 13 the potential for TB infection and spread is high among homeless populations.…”
Section: Introductionmentioning
confidence: 99%